DECISION SUPPORT SYSTEM FOR BOARDING HOUSE RECOMMENDATIONS AROUND UPY BASED ON RULES AND SPATIAL WEB - Ganang Prihatma Artha; Muhammad Fairuzabadi; Aditya Wahana (CV. Fahr Publishing, 2024)
Boarding houses, often referred to simply as